Transforming economics : perspectives on the critical realist project - Lewis, Paul, 1971- (Economics as social theory., 2004)
Leading authors within economics have come together here to discuss the contribution of critical realism to economics. A wide range of opinions are offered from Ben Fine to Clive Grainger and the results are explosive.